Behavioral Hypotheses of Internal Control. - Carmichael, D. R. (The Accounting Review, 1970)
This paper develops the behavioral hypotheses which underly the design, operation, and audit of internal control systems. The traditional conception of the organizational setting of the internal control system in accounting literature resembles very closely what organization theorists have referred to as the formal organization. When the traditional behavioral hypotheses are examined in the light of current thinking in organization theory, however, some doubt is cast on the validity of the traditional hypotheses. Although the traditional hypotheses are not conclusively invalidated in this paper, enough doubt should exist to stimulate formulation of hypotheses more in agreement with organizational reality.